Prenatal transplantation of mesenchymal stem cells to treat osteogenesis imperfecta - Chan, Jerry K. Y.; Götherström, Cecilia (Frontiers in Pharmacology, 2014)
Osteogenesis imperfecta (OI) can be a severe disorder that can be diagnosed before birth. Transplantation of mesenchymal stem cells (MSC) has the potential to improve the bone structure, growth, and fracture healing. In this review, we give an introduction to OI and MSC, and the basis for pre- and postnatal transplantation in OI. We also summarize the two patients with OI who have received pre- and postnatal transplantation of MSC. The findings suggest that prenatal transplantation of allogeneic MSC in OI is safe. The cell therapy is of likely clinical benefit with improved linear growth, mobility, and reduced fracture incidence. Unfortunately, the effect is transient. For this reason, postnatal booster infusions using same-donor MSC have been performed with clinical benefit, and without any adverse events. So far there is limited experience in this specific field and proper studies are required to accurately conclude on clinical benefits of MSC transplantation to treat OI.